Effects of castor oil on escherichia coli K011 growth and fermenting activities during anaerobic fermentation - Ennry, Esut (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Bioethanol is one of the biofuel that is widely studied presently. This is due to the decreasing of fossil fuel. Researchers are making various efforts to find other fuel alternative to resolve this issue. One way is the production of bioethanol from lignocellulosic waste. Thus, there is a very big opportunity in developing fuel ethanol from agricultural residue and other lignocellulosic feedstock because it is low in cost. Bioethanol productions majoriy used are fermentation technique. One of major problem in fermentation is ethanol accumulation. Therefore with existence of castor oil this problem can be solved. Ability of castor oil in absorption of ethanol gives huge impact in the fermentation process. In this project Escherichia coli KO 11 is main fermenting agent toward glucose. But from the result existence of castor oil in fermentation broth give some effects toward the growth and fermenting activities. There are better results obtained from experiment conducted without castor oil. This could be due to several factors. Firstly toxicity character that castor oil has affected E. coli KO 11 activities. Then, another factor is glucose is not the best substrate for E. coli KO ~ 1 to consume. Therefore, for better production of ethanol for E. coli KO 11 xylose is more preferred.